THE SYSTEM OF IMAGES IN HAMZA'S POETRY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In this article, the poet, prose writer and dramatist Hamza Hakimzoda Niyazi, who contributed to the renewal of artistic thinking in the beginning of the 20th century, analyzes the specific aspects and poetic images of the poet.